Human Complement C4B Allotypes and Deficiencies in Selected Cases With Autoimmune Diseases - Zhou, Danlei; Rudnicki, Michael; Chua, Gilbert T.; Lawrance, Simon K.; Zhou, Bi; Drew, Joanne L.; Barbar-Smiley, Fatima; Armstrong, Taylor K.; Hilt, Miranda E.; Birmingham, Daniel J.; Passler, Werner; Auletta, Jeffrey J.; et al. (Frontiers in Immunology, 2021)
Human complement C4 is one of the most diverse but heritable effectors for humoral immunity. To help understand the roles of C4 in the defense and pathogenesis of autoimmune and inflammatory diseases, we determined the bases of polymorphisms including the frequent genetic deficiency of C4A and/or C4B isotypes. We demonstrated the diversities of C4A and C4B proteins and their gene copy number variations (CNVs) in healthy subjects and patients with autoimmune disease, such as type 1 diabetes, systemic lupus erythematosus (SLE) and encephalitis. We identified subjects with (a) the fastest migrating C4B allotype, B7, or (b) a deficiency of C4B protein caused by genetic mutation in addition to gene copy-number variation. Those variants and mutants were characterized, sequenced and specific techniques for detection developed. Novel findings were made in four case series. First, the amino acid sequence determinant for C4B7 was likely the R729Q variation at the anaphylatoxin-like region. Second, in healthy White subject MS630, a C-nucleotide deletion at codon-755 led to frameshift mutations in his single C4B gene, which was a private mutation. Third, in European family E94 with multiplex lupus-related mortality and low serum C4 levels, the culprit was a recurrent haplotype with HLA-A30, B18 and DR7 that segregated with two defective C4B genes and identical mutations at the donor splice site of intron-28. Fourth, in East-Asian subject E133P with anti-NMDA receptor encephalitis, the C4B gene had a mutation that changed tryptophan-660 to a stop-codon (W660x), which was present in a haplotype with HLA-DRB1*04:06 and B*15:27. The W660x mutation is recurrent among East-Asians with a frequency of 1.5% but not detectable among patients with SLE. A meticulous annotation of C4 sequences revealed clusters of variations proximal to sites for protein processing, activation and inactivation, and binding of interacting molecules.